탄소고정효과를 고려한 산림벌기령 분석 - 민경택 (한국농촌경제연구원, 2011)
This paper analyzes an optimal forest cutting age for even-aged forest management of Gangwon pines and Korean pines when the carbon sequestration service of a forest is considered. Carbon price and tax will affect the optimal forest cutting age and the carbon storage in forests. It is shown that inclusion of the benefits from carbon sequestration results in cutting ages a bit longer than when the carbon sequestration service has not value. The optimal cutting age is affected by how to deal with the carbon released after harvesting, which is a key issue of “harvested wood products” in the UNFCCC. The more the carbon contents in harvested wood products are, the shorter the optimal cutting age is. And the supply curve of forest carbon sequestration service is inelastic with carbon price. Therefore it is important to maintain the cycle of harvest and replant in the forest carbon offset scheme.
Keywords: 기후변화; 벌기령; 탄소고정; 파우스트만 공식; climate change; forest cutting age; carbon sequestration; Faustmann's formula